2022
DOI: 10.1002/ente.202200433
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis in Solid Hydrogen Storage: Recent Advances, Challenges, and Perspectives

Abstract: Catalysis is at the core of previous energy transition. It has enabled the use of oil and natural gas as our primary energy sources in unprecedented ways and led to feedstocks enabling exceptionally high living standards in human history. In a decarbonized economy with hydrogen as the new energy vector, catalysis is already playing a key role in producing hydrogen. However, catalysts for the effective storage of hydrogen must be advanced. Many solid hydrogen storage materials such as magnesium‐based hydrides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 704 publications
(825 reference statements)
0
11
0
Order By: Relevance
“…The introduction of a suitable catalyst or catalytic additive is the simplest and most effective way to reduce the operating temperatures and enhance the reaction kinetics for hydrogen storage in the Mg/MgH 2 system. Over the past few decades, various catalysts and catalytic additives have been developed to improve the hydrogen storage performance of MgH 2 , including transition metal and its alloys (e.g., Ti, V, Nb, Ni, ZrNi, Ti 2 Ni, ZrMn 2 ), metal hydrides (e.g., TiH 2 , ZrH 2 , NbH x , VH x ), metal halides (e.g., NbF 5 , TiCl 3 , TiF 3 , ZrCl 4 ), metal oxides (e.g., TiO 2 , ZrO 2 , Nb 2 O 5 , V 2 O 3 ), metal carbides (e.g., Ti 3 C 2 , Nb 4 C 3 ), sulfides (e.g., NiS), nitrides (e.g., NbN), phosphides (e.g., Ni 2 P), and carbon-based materials (e.g., carbon nanotubes, graphene). Considerable work has also revealed that nanosized catalysts usually delivered much enhanced catalytic activity than their bulk counterparts. ,, Chen et al reported that the introduction of 4 mol % porous Ni nanofibers dramatically reduced the dehydrogenation peak temperature from 385 to 244 °C, while it was only decreased to 340 °C when 4 mol % Ni powders were introduced . By doping V nanosheets (NSs), Lu et al observed hydrogen release at 187.5 °C, but no hydrogen was detected when using bulk V as additives even after heating to 270 °C .…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of a suitable catalyst or catalytic additive is the simplest and most effective way to reduce the operating temperatures and enhance the reaction kinetics for hydrogen storage in the Mg/MgH 2 system. Over the past few decades, various catalysts and catalytic additives have been developed to improve the hydrogen storage performance of MgH 2 , including transition metal and its alloys (e.g., Ti, V, Nb, Ni, ZrNi, Ti 2 Ni, ZrMn 2 ), metal hydrides (e.g., TiH 2 , ZrH 2 , NbH x , VH x ), metal halides (e.g., NbF 5 , TiCl 3 , TiF 3 , ZrCl 4 ), metal oxides (e.g., TiO 2 , ZrO 2 , Nb 2 O 5 , V 2 O 3 ), metal carbides (e.g., Ti 3 C 2 , Nb 4 C 3 ), sulfides (e.g., NiS), nitrides (e.g., NbN), phosphides (e.g., Ni 2 P), and carbon-based materials (e.g., carbon nanotubes, graphene). Considerable work has also revealed that nanosized catalysts usually delivered much enhanced catalytic activity than their bulk counterparts. ,, Chen et al reported that the introduction of 4 mol % porous Ni nanofibers dramatically reduced the dehydrogenation peak temperature from 385 to 244 °C, while it was only decreased to 340 °C when 4 mol % Ni powders were introduced . By doping V nanosheets (NSs), Lu et al observed hydrogen release at 187.5 °C, but no hydrogen was detected when using bulk V as additives even after heating to 270 °C .…”
Section: Introductionmentioning
confidence: 99%
“…In general, pure Mg in the micron sizes displays low reactivity toward H 2 molecules because it does not own d-band electrons that are particularly important to promote the dissociation of hydrogen molecules by interacting with the hydrogen antibonding orbital. , Furthermore, MgO or Mg­(OH) 2 is readily generated on the surface of metallic Mg that hinders the dissociative adsorption of H 2 molecules or the transfer of H atoms from the surface to bulk. , An effective catalyst or catalytic additive has proved effective in improving hydrogen sorption kinetics of the Mg/MgH 2 system. ,, Typically, transition metals and their compounds including halides, oxides, carbides, nitrides, and hydrides have been extensively studied for their capability to promote the breaking and rebonding of H–H and Mg–H bonds. , For example, Ti, Zr, Co, Fe, V, Nb, and Ni are quite effective in expediting the hydrogen storage process of Mg/MgH 2 . It was demonstrated that 10 wt % Ni nanoparticle-modified MgH 2 started releasing hydrogen from 130 °C .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In recent years, more and more attention has been paid to the generation of hydrogen via formic acid, ammonia borane, metal hydrides, and their derivatives because of their high theoretical hydrogen yield. [5][6][7][8] Amongst various hydrogen production and storage methods, hydrolysis of borohydrides, especially NaBH 4 , has gained much attention due to its high hydrogen storage capacity (10.8 wt% for NaBH 4 ), high H 2 purity, mild operation conditions, high safety and environmentally benign nature. [9][10][11][12][13] Besides, great achievements have been made in the simplified synthesis and regeneration of NaBH 4 , which facilitates the development of the hydrogen energy process chain and the hydrogen economy.…”
Section: Introductionmentioning
confidence: 99%